2019
DOI: 10.12669/pjms.35.1.373
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of sonographic fetal weight estimation in full-term singleton pregnant women

Abstract: Objectives: To investigate the factors which might influence the sonographic fetal weight estimation (SFWE) accuracy. Methods: This prospective study was conducted among 949 singleton term pregnant women who delivered at a tertiary center, from January 2017 to December 2017. All participants’ maternal (i.e. parity, age, body mass index and gestational weight gain during pregnancy), fetal sonographic (i.e. fetal presentation, amniotic fluid index, localization of placenta and estimated fetal weight) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In our analysis, prepregnancy and delivery BMI, prepregnancy and delivery weight and height, GA, the use of IVF, the time interval between the ultrasound and birth, the fetal presentation, the BPD, the HC, the AC, the FL, and the amniotic volume were not found to be statistically related with SFWE, which is in line with the findings of several reports ( 5 , 10 - 13 ) but contradicts those of other studies ( 14 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our analysis, prepregnancy and delivery BMI, prepregnancy and delivery weight and height, GA, the use of IVF, the time interval between the ultrasound and birth, the fetal presentation, the BPD, the HC, the AC, the FL, and the amniotic volume were not found to be statistically related with SFWE, which is in line with the findings of several reports ( 5 , 10 - 13 ) but contradicts those of other studies ( 14 , 15 ).…”
Section: Discussionsupporting
confidence: 92%
“…The Hadlock formula is one of the oldest and most popular formulas in China. Research has shown that a number of maternal or fetal factors may affect the accuracy of sonographicbased fetal weight estimation (SFWE) ( 5 ), which is used to predict FW. An SFWE that falls within 10.0% of the neonatal birth weight is considered accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the EFW was assessed by determining the absolute value of the difference between the PBW and the actual birth weight, divided by the latter; this difference defined the “EFW error” and was expressed as a percentage for each examination in line with other publications assessing EFW accuracy 12,14,18,21 . EFW errors greater than 10% were identified and defined as inaccurate EFW.…”
Section: Methodsmentioning
confidence: 99%
“…To limit the biases associated with the variation of the intervals between the ultrasound scan and birth (or Δ, expressed as days between the delivery and the ultrasound), the projected birth weight (PBW) was determined by adding to the EFW assessed on the day of the ultrasound 30 g per day until the birth 19,20 The accuracy of the EFW was assessed by determining the absolute value of the difference between the PBW and the actual birth weight, divided by the latter; this difference defined the "EFW error" and was expressed as a percentage for each examination in line with other publications assessing EFW accuracy. 12,14,18,21 EFW errors greater than 10% were identified and defined as inaccurate EFW. Because of the inclusion of both novice operators and extreme fetal weights in the sample (no non-inclusion criteria related to fetal growth restriction or macrosomia), an additional category of seriously inaccurate EFW errors (≥15%) was also defined and reported.…”
Section: Fetal Weight Estimationmentioning
confidence: 99%
See 1 more Smart Citation